Antidepressants in Type II Versus Type I Bipolar Depression: A Randomized Discontinuation Trial. Issue 5 (October 2015) - Vöhringer, Paul A.; Ostacher, Michael J.; El-Mallakh, Rif S.; Holtzman, Niki S.; Thommi, Sairah B.; Whitham, Elizabeth A.; Sullivan, Matthew C.; Baldassano, Claudia F.; Goodwin, Fredrick K.; Baldessarini, Ross J.; Ghaemi, S. Nassir
Abstract : Background: We sought to test the hypothesis that antidepressants (ADs) may show preferential efficacy and safety among patients with type II bipolar disorder (BD, BD-II) more than patients with type I BD (BD-I). Methods: Patients with Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, BD-I (n = 21) and BD-II (n = 49) in acute major depressive episodes were treated with ADs plus mood stabilizers to euthymia sustained for 2 months and then randomized openly to continue or discontinue ADs for up to 3 years. Outcomes were episode recurrences and changes in standardized symptom ratings. Results: In follow-up averaging 1.64 years, both subgroups showed improvement in depressive episode frequency with AD continuation, but contrary to the hypothesis, more improvement was seen in BD-I than in BD-II (for type II, mean [standard deviation] decrease in depressive episodes per year, 0.21 [0.26]; for type I, mean (SD) decrease, 0.35 [0.15]). Subjects with BD-II who continued on ADs had slightly more depressive, but fewer manic/hypomanic, episodes than subjects with BD-I. No notable differences were seen in either group in time to a recurrence of mood episodes or total time-in-remission. Conclusions: The findings do not confirm the hypothesis that long-term AD treatment in patients with BP-II has better outcomes than in patients with BD-I, except somewhat lower risk of manic/hypomanic episodes.